A megbocsátás hatása a párkapcsolati működésre - PÁL, Tünde; LAKATOS, Csilla (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
The Effect of Forgiveness on the Way Relationships Work. Forgiveness belongs to those coping strategies with a strong religious base, which, by focusing on strengths and development opportunities, help people to normalize their injured, disturbed relationships, to reduce the frequency of con-flicts, and to help preventing the aggravation of problems in the future; in this way, it is important not only for religious people. Forgiveness, as well as the functioning of relationships, are affected by both personality, environmental, and relationship factors. Taking into consideration the personality traits, for-giveness can also be understood as a disposition, as a relatively stable attitude of the personality manifested in various life situations, as such a psychological ad-aptation, through which people willing to forgive are actively seeking to normal-ize their intra- and interpersonal relations. In our paper, we review the role of forgiveness in harmonizing the relation-ships, the way a helping professional can use it in the process of working through an injury. For a more complete view, we have built our psychological approach on the theological, biblical definition of forgiveness and on the analogy of the Divine Forgiveness.